Bank capital and profitability: evidence from a global sample. Issue 9 (13th June 2021) - Coccorese, Paolo; Girardone, Claudia
Abstract : This study employs bank-level data for a global sample of 125 countries to examine the relationship between capital and profitability for a period of 19 years (2000–2018) that includes both normal and crisis time. Our evidence suggests that bank capital is positively related to bank profitability, although the estimated impact is relatively weak. The relationship depends on environmental conditions as well as bank size. It is typically stronger in crisis periods, in lower and middle income countries and for larger banks (but not for Global Systemically Important Banks, or GSIBs). Finally, for banks operating in more corrupt environments, the same increase in capital is associated with more profitable institutions compared with banks based in countries with lower corruption levels. Our findings are robust to different specifications of the baseline model, and carry useful implications for policy reforms aimed at ensuring stability to the banking sector globally.